HUBUNGAN KADAR PLUMBUM (Pb) DALAM DARAH DENGAN JUMLAH ERITROSIT PADA IBU HAMIL - Diah Prihatiningsih; I Gusti Putu Agus Ferry Sutrisna Putra (Jurnal Education and Development, 2023)
Heavy metal exposure can affect human health. One of them is exposure to lead metal which is toxic which can accumulate in the human body. Exposure to lead in the human body has the effect that it can affect the hematological system by interfering with heme synthesis which can shorten the life of red blood cells (erythrocytes) causing anemia. The purpose of this study was to determine the relationship between blood lead levels and the number of erythrocytes in pregnant women in the Puskesmas Abiansemal I Badung. This research is an analytic study with a cross sectional design. The population in this study were all pregnant women who live in the Puskesmas Abiansemal I Badung. The number of samples as many as 36 respondents were taken by purposive sampling technique. The results of this descriptive study showed that the blood lead levels of pregnant women averaged 22.06 ± 7.027 g/dL with a minimum value of 6.22 g/dL and a maximum value of 30.52 g/dL. The results of bivariate analysis showed that there was no significant relationship between blood lead levels and the number of erythrocytes in pregnant women (p = 0.170).